Indexing HDFS data in PDW: splitting the data from the index - Gankidi, Vinitha Reddy; Teletia, Nikhil; Patel, Jignesh M.; Halverson, Alan; DeWitt, David J. (Very Large Data Bases, 2014)
There is a growing interest in making relational DBMSs work synergistically with MapReduce systems. However, there are interesting technical challenges associated with figuring out the right balance between the use and co-deployment of these systems. This paper focuses on one specific aspect of this balance, namely how to leverage the superior indexing and query processing power of a relational DBMS for data that is often more cost-effectively stored in Hadoop/HDFS. We present a method to use conventional B+-tree indices in an RDBMS for data stored in HDFS and demonstrate that our approach is especially effective for highly selective queries.